Wired [compact disc, unabridged] - Garwood, Julie (Brilliance Audio, 2017)
Allison Trent is a computer genius recruited to work for the FBI. She is finding it difficult to keep her guard up around FBI agent Liam Scott. After a year in the bureau, someone has stolen the program Allison set up. Will they find who did it and still keep their hearts?